Out-Of Seismic Performance of Bed-Joint Reinforced Autoclaved Aerated Concrete (aac) Infill Walls Damaged Under Cyclic In-Plane Displacement Reversals - İlki, Alper; Demir, Uğur; Halıcı, Ömer Faruk; Zabbar, Yassin (Elsevier Sci Ltd, 2023)
The infill walls made of Autoclaved Aerated Concrete (AAC), which is a lightweight, fire resistant and energy efficient material, provide effective insulation solutions for building types of structures and becoming more and more popular in earthquake prone regions. Although the number of experimental tests examining the seismic response of clay brick infills is extensive, the amount of prior research on infill walls built of AAC blocks is rather limited. Past research revealed that the use of bed-joint reinforcement is one of the promising solutions to improve the global seismic response of masonry walls by enhancing strength and displacement capacity. In this study, the out-of-plane (OOP) seismic performance of AAC infill walls with flat-truss and innovative cord-type bed-joint reinforcement is experimentally evaluated. Also, consideration is given to the prior in-plane (IP) damage, which was found to degrade the seismic performance of infills in OOP direction. For this purpose, three IP and four OOP, in total, seven experimental tests were performed on four full-scale AAC infill wall specimens. The test parameters were selected in such a way as to make it possible to parametrically compare the OOP performance of AAC infills with flat-truss and cord-type bed-joint reinforcements with unreinforced AAC infill walls, together with the effect of prior IP damage on the OOP response of unreinforced AAC infill walls. It was found that the use of innovative cord-type bed-joint reinforcement improved the OOP strength to a similar extent to what was obtained from the truss-type reinforced specimen. In terms of ultimate displacement and energy dissipation capacity enhancement, the specimen with cord-type reinforcement performed better. In addition, the damages formed due to IP cyclic displacement reversals up to 0.005 drift ratio, which is defined as the drift limit for buildings with brittle infill walls in certain design codes, resulted in a significant reduction in the OOP strength and stiffness properties of AAC infills. The theoretical OOP strength calculations were found to provide unconservative strength values for the IP-damaged specimens.
Scientific and Technological Research Council of Turkey (TUBITAK); [1649B031700370]
All of the sources of funding for the work described in this publication are acknowledged below: 2211-a, scholarship reference number 1649B031700370. PhD scholarship granted to Omer Faruk Halici
Keywords: Behavior; Bed-joint reinforcement; Experimental seismic performance evaluation; Frames; Autoclaved aerated concrete (aac); Infill walls; Sliding joints; Capacity; In-plane and out-of-plane behavior; Masonry